Effect of Halopriming on Sunflower Seed Germination and Seedling Establishment under Saline Environment (Biological Sciences - PJSIR, 2004)
. The effect of halopriming of sunflower seeds with inorganic salts (KNO3 and K2SO4) on seed germination and seedling establishment under salt stress (200 mM NaCl) was studied. Priming of sunflower seeds using low concentration of salt improved germination. Hundred percent germination and better seedling establishment were recorded with 2% K2SO4 at 200 mM NaCl salt stress. In plant tissues, higher concentration of Na+ (0.61%) was observed in case of 2% KNO3 and minimum with 2% K2SO4 (0.26%) and higher concentration of K+ was observed with 2% K2SO4 followed by 1% K2SO4 and 2% KNO3. Maximum concentrations of Ca and Mg in plant tissues were found with 2% K2SO4.